PERANAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Adelia Marwah Ujung; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (Bajang Institute, 2023)
In an organization there is no escape from institutional data archiving problems. Where a system is needed that appears in this advanced era where information systems are very influential on leaders in an education in planning something in solving problems that arise in an education so that the goals of the education will be achieved as planned. Management information systems are also very useful for an education because it can ease the leadership's task of completing accurate and fast data and then processing it into information that can help leaders plan education.